2001
DOI: 10.1159/000054216
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Cyclosporine-Induced Nephrotoxicity in Humans: A Role for Nitric Oxide?

Abstract: Background: The causes for the nephrotoxicity of cyclosporine A (CsA) have not been fully elucidated. Intrarenal vasoconstriction induced by several different mediators, both in humans and experimental animals, have been proposed. Methods: We studied prostaglandin metabolites, endothelin and nitric oxide in kidney transplant patients receiving their first CsA dose. Prostaglandin metabolites in the urine and endothelin and nitric oxide (NO2/NO3) in urine and plasma were measured in 14 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 16 publications
5
18
0
Order By: Relevance
“…An inhibition of COX-2 expression and consequently an inhibition of prostanoid formation by calcineurin inhibitors also fits well with in vitro and in vivo data. In this context, it has been found that CsA decreases PGE 2 formation in cultures of vascular smooth muscle cells (33) and that calcineurin inhibitors decrease the renal excretion of vasodilatory prostanoids, like PGE 2 and prostacyclin, in rats and humans (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…An inhibition of COX-2 expression and consequently an inhibition of prostanoid formation by calcineurin inhibitors also fits well with in vitro and in vivo data. In this context, it has been found that CsA decreases PGE 2 formation in cultures of vascular smooth muscle cells (33) and that calcineurin inhibitors decrease the renal excretion of vasodilatory prostanoids, like PGE 2 and prostacyclin, in rats and humans (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…However, participation of NO, an important renal vasodilator, is highly suggested to participate in CsA-induced nephrotoxicity. Gossmann et al 5 reported that acetylcholine-induced vasodilatation is impaired in vascular beds of CsAtreated animals, which may indicate deficiency of endothelial NO synthesis. However, this conclusion can also be referred to the enhanced generation of free radicals in CsA-induced nephrotoxicity which is able to inactivate NO.…”
Section: Discussionmentioning
confidence: 99%
“…Renal vasoconstriction is attributed to a disturbance in the complex dynamic interaction of predominating vasoconstrictors with counteracting vasoactive substances. 2,[4][5][6][7][8] Moreover, the oxidative damage in the body induced by reactive oxygen species and lipid peroxidation products is frequently reported in the CsA nephrotoxicity. [9][10][11] The involvement of free radical species in CsA nephrotoxicity was supported by the fact that many antioxidants and free radical scavengers provide marked functional protection.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, CsA causes several pathophysiological changes that have been regarded crucial for the side effects such as direct vasoconstriction [7], increased sympathetic and angiotensin activities [8,9], endothelin release [10] as well as endothelin-mediated vasoconstriction [11] and altered renal metabolism of arachidonic acid favoring a vasoconstrictor prostanoid profile [12]. Endothelial dysfunction may also contribute to the side effects of CsA resulting in renal arterial vasoconstriction and subsequent nephrotoxicity [13,14] and hypertension [15]. Vascular relaxation elicited by acetylcholine [16], bradykinin [17], substance P [18], calcium ionophore A23187 [17], and prostaglandin E 1 [19] are remarkably impaired by CsA.…”
Section: Introductionmentioning
confidence: 99%